SLAUGHTERHOUSE INCOMING STRATEGY IN KUPANG CITY (International Conference of Graduate School on Sustainability (ICGSS), 2020)
ABSTRACT This thesis is entitled Analysis of the Effectiveness and Contribution of the Levy for the Kupang Slaughterhouse to the Original Regional Income of Kupang City. The problem that will be examined in this thesis is what is the level of effectiveness and contribution of slaughterhouse (RPH) levies on local revenue (PAD) in Kupang City ?. This study aims to determine how the level of effectiveness and contribution of the slaughterhouse levies to the local income of Kupang City. This research uses qualitative and quantitative approaches. The types of data used are primary and secondary data. The data collection techniques used were observation, interview, documentation and literature study techniques. The results of this study indicate that the Slaughterhouse in Kupang City increases sales on holidays due to the very high demand for meat supply. In terms of effectiveness, the revenue from animal slaughterhouses in Kupang City has increased every year with an average of 91.05% from 100%. In 2014 amounted to 80.47% or Rp.523,106,000. 2015 amounted to 85.55% or Rp.556,109,000. In 2016 amounted to 98.53% or Rp.640,482,000, in 2017 it reached 99.62% or Rp. 647,557,000. Keywords: Slaughterhouse, Incoming, Strategy